The Relationship of Illustrated Health Warnings on Cigarette Packaging to Quitting Intentions of Pamulang University Students - Ramadhan, Gaung Eka (Medical Science Journal for Advance Research, 2021)
This study analyzes the relationship between pictorial health warnings on cigarette packaging and the intention to quit smoking for Pamulang University students. This research design uses quantitative analysis with a cross-sectional method complemented by qualitative respondents, namely Pamulang University students totaling 100 respondents. This research was conducted from December 2019 – January 2020. The data analysis used univariate analysis, bivariate analysis, and multivariate analysis. The results showed that there was a significant relationship between perceptions of pictorial health messages and the intention to stop smoking, the p-value indicated this: 0.000 and the OR value 43.5; there is a significant relationship between knowledge and intention to stop smoking with a p-value: 0.000 and OR value 75.6;